Praktik Peradilan dan Kesetaraan Gender: Analisis Implementasi PERMA No. 3 Tahun 2017 di Pengadilan Syariah Banda Aceh, Indonesia - Fitri, Sulis Mai; Melayu, Hasnul Arifin; Fithria, Nurul (Prodi Tata Negara (Siyasah) IAIN Langsa, 2024)
Discriminatory treatment and gender stereotypes against women in the justice system are directly related to women's accessibility to justice. The more women experience discrimination and negative stereotypes, the more limited their access to justice becomes. The implementation of Supreme Court Regulation (PERMA) No. 3 of 2017 concerning Guidelines for Adjudicating Cases Involving Women in Conflict with the Law has not been effectively carried out. For instance, some judges in the trial process have not adhered to the guidelines set out in PERMA No. 3 of 2017. In reality, there are still judges who make belittling, blaming, intimidating statements, and use loud voices against women in conflict with the law, which can undermine women's mentality in court. In response to these conditions, the Supreme Court, as the highest judicial institution in Indonesia, has initiated steps to gradually eliminate discriminatory treatment against women in conflict with the law in judicial practices in Indonesia. This study aims to examine the efforts made by judges in implementing PERMA No. 3 of 2017 at the Banda Aceh Sharia Court and to explore the perspectives of Sharia Court judges regarding the implementation of PERMA No. 3 of 2017. The research uses a qualitative method with a field research approach. This study indicates that there are still challenges in implementing PERMA No. 3 of 2017 at the Banda Aceh Sharia Court. However, efforts are being made to reduce discrimination and negative stereotypes against women in conflict with the law. This research contributes to providing insights into the importance of implementing guidelines to reduce discriminatory treatment and offering recommendations to improve the effectiveness of PERMA No. 3 of 2017 in addressing gender discrimination issues in Indonesian courts.